Effectiveness and safety of selected traditional Chinese medicine injections in patients with combined diabetes mellitus and coronary heart disease: A systematic review and network meta-analysis of randomized clinical trials - Shen, Hailiang; Zhou, Ping; Shen, Luyao; Ju, Chenhao; Du, Haixia; Qu, Xianguo (Frontiers in Pharmacology, 2023)
In view of the high morbidity and mortality of Diabetes mellitus - coronary heart disease (DM-CHD) in diabetes, the combination therapy of traditional Chinese medicine injections (TCMIS) and conventional therapy (CT) is receiving extensive attention. Therefore, the effectiveness and security of CT with TCMIS in the therapy of DM-CHD were compared by systematical review and network meta-analysis.According to the preset inclusion criteria and exclusion criteria, we searched seven electronic literature databases were searched from their inceptions to JAN 5,2022, to obtain the relevant RCT literature on the therapy of DM-CHD with TCMIS. Two researchers independently reviewed the papers, two other researchers worked in extracting data and quality assessment of the included literature. The primary outcomes were total effective rate. The secondary outcomes included electrocardiogram (EGG)effective rate, the effective rate of angina pectoris, fasting blood glucose (FBG), 2-hour postprandial blood glucose (PBG), hemoglobinA1c (HbA1c), total cholesterol (TC) and triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), frequency of angina pectoris, and duration of angina pectoris. We adopted stata16.0 software for the systematic review and network meta-analysis.A total of 53 trials involved 4619 patients and one of the following 16 TCMIs: Danhong, Danshen, Gualoupi, Gegen, Chuanxiongqin, Danshenchuanxiongqin, Shenmai, Shenqi, Xixin, Xuesaitong, Shuxuetong, Guanxinning, Kudiezi, Ciwujia, Xingding, Shuxuening. The meta-analysis revealed that Chuanxiongqin injection was superior to all other therapies in improving the total effective rate, [vs. CT odds ratio (OR): 14.52, 95% confidence interval (CI): 4.13–51.02], vs. Xuesaitong injection (OR: 7.61, CI: 1.25–46.40), and vs. Danshenchuanxiongqin injection (OR: 3.98, CI: 1.03–15.28)]. Xixin injection+CT was superior to CT only for ECG response rate (OR: 5.44, CI: 1.55–19.18). Shenmai injection+CT was superior to CT in effective rate of angina (OR: 11.05, CI: 2.76–44.28). There was not different significantly in the comparisons of frequency of angina pectoris and duration of angina pectoris; but,this may be due to the lack of enough data. Basing on our study, TCMIs combined with CT takes important role in the treatment of DM-CHD, and its curative effect is better than conventional therapy. Nevertheless, properly designed RCTs are required to validate our conclusions in the future.